3PC-004 Physicochemical stability of cefepime in polypropylene syringes and in elastomeric devices. (24th March 2020) - D'huart, E; Zenier, H; Vigneron, J; Charmillon, A; Demore, B
Abstract : Background and importance: Cefepime is a fourth generation cephalosporin used to treat severe infectious. For β-lactam antibiotics, publications have demonstrated that continuous administration is the preferred mode of administration. To the best of our knowledge, no stability data for cefepime solutions at 110 mg/mL in polypropylene syringes or at 50 mg/mL in elastomeric devices have been published. Aim and objectives: The objectives of the study were to assess the stability of cefepime solutions (1) at 110 mg/mL, in 0.9% sodium chloride (0.9% NaCl) or 5% dextrose (D5W), in polypropylene syringes at 20–25°C and (2) at 50 mg/mL, in 0.9% NaCl, in elastomeric devices at 37°C, after preparation and after storage for 6, 24 and 48 hours. Material and methods: Three preparations for each condition were made. For each analysis, one sample was taken from each preparation and analysed by high performance liquid chromatography. The method was validated according to the International Conference on Harmonisation Q2 (R1). Physical stability was evaluated by visual and subvisual inspection with a nephelometer. pH values were measured. Results: In syringes, for each solvent, cefepime solutions at 110 mg/mL retained more than 90% of the initial concentration after 24 hours. No visual modification and no turbidity were observed. After 48 hours, the solutions retained around 83% of the initial concentration and pH values increased with the addition of 1 pH unit compared with the initial value. In elastomeric devices, cefepime solution in 0.9% NaCl at 50 mg/mL retained more than 90% of the initial concentration over a period of 6 hours. After 24 and 48 hours, the solutions retained around 83% and 59% of the initial value, respectively. After 6 hours, visual colour modifications were observed. Under this condition, the initial pH value was 4.81 and 6.18 after 24 hours. Conclusion and relevance: The stability of cefepime in 0.9% NaCl and D5W at 110 mg/mL was demonstrated for 24 hours in syringes at 20–25°C. These stability data provide additional knowledge when performing continuous infusion of cefepime in syringe. In elastomeric devices, cefepime solution at 50 mg/mL in 0.9% NaCl stored at 37°C was unstable. These preparations are not recommended. In view of these results, the stability of cefepime in D5W in elastomeric devices was not studied. References and/or acknowledgements: No conflict of interest.